THE EFFECT OF PROBLEM BASED LEARNING MODEL STUDENTS ACHIEVEMENT ON STATIC FLUID TOPIC AT YEAR XI OF SMA NEGERI2 LINTQNGNIHUTA ACADEMIC YEAR 2015/2016 - Hutasoit, Novianti; Sirait, Motlan (JURNAL IKATAN ALUMNI FISIKA, 2016)
This research is aimed to know and describe the students Achievement using problem based learning and conventional learning about static fluid topic . This research employed a quasi experimental pretest and posttest with control design. The populations were 60 students grade Xl-science in SMAN 2 Lintongnihuta academic year 2015/2016. The samples consist of two classes, one class with 30 students as experiment class and one class as control class with 30 students, while the sampling technique used purposif sampling. Research instrument used essay test. The data obtained in the study were analyzed by the computer program Ms.Excel. From the research the pre-test average value of outcomes experiment class 26.66 and control class 27.83, after giving the treatment the post-test with the average value of outcomes experiment class 59.66 and control class 49.50. The result of t test Uunt = 3.158 while ttabie= 1.661. Because tc<>unl>ttabie(3.158> 1.661) so Ho rejected. The result showed that students achievement in experiment class had been treated with problem based learning model have significantly different from control class which had been treated with conventional learning. In addition, the improvement of PBL in experiment class was greater than in control class. This meant implementation problem based learning has a significant effect toward student achievement.